Cultural Marxism: far-right conspiracy theory in Australia's culture wars. (1st November 2020) - Busbridge, Rachel; Moffitt, Benjamin; Thorburn, Joshua
ABSTRACT: As a conspiracy promoted by the far-right, Cultural Marxism has gained ground over the past quarter century. In its dominant iteration, the US-originating conspiracy holds that a small group of Marxist critical theorists have conspired to destroy Western civilisation by taking over key cultural institutions. Yet what does such a conspiracy look like in a transnational context – and how are such conspiracy theories adapted for local use? In this article, we trace Cultural Marxism's use and function in Australia's recent culture wars, asking when, where and in what contexts the conspiracy is invoked in the Australian political and media landscape. Our analysis examines the ways in which Cultural Marxism has moved from the 'fringe' to the 'mainstream', revealing the porous nature of divisions on the contemporary Australian right as well as differences between 'old' and 'new' right. We pay particular attention to the localised use of the conspiracy in the 'Safe Schools' controversy of 2016–2017, whereby Cultural Marxist tropes were imbued with local concerns about sexuality and gender issues. The article provides an important illustration and analysis of the ways in which transnational conspiracy theories and tropes of the far-right can be translated, adapted and used in different national contexts.